Spirosoma utsteinense sp. nov. isolated from Antarctic ice-free soils from the Utsteinen region, East Antarctica. Issue 3 (17th March 2021) - Tahon, Guillaume; Lebbe, Liesbeth; Willems, Anne
Abstract : Between 2014 and 2016, 16 Gram-stain-negative, aerobic, rod-shaped and yellow-orange pigmented bacteria were isolated from exposed soils from the Utsteinen region, Sør Rondane Mountains, East Antarctica. Analysis of their 16S rRNA gene sequences revealed that the strains form a separate cluster in the genus Spirosoma, with Spirosoma rigui KCTC 12531 T as its closest neighbour (97.8 % sequence similarity). Comparative genome analysis of two representative strains (i.e. R-68523 T and R-68079) of the new group with the type strains of Spirosoma rigui (its closest neighbour) and Spirosoma linguale (type species of the genus), yielded average nucleotide identity values of 73.9–78.7 %. Digital DNA–DNA reassociation values of the two strains and these type strains ranged from 20.3 to 22.0 %. The predominant cellular fatty acids of the two novel strains were summed feature 3 (i.e. C16 : 1  ω 7 c and/or iso-C15 2-OH), C16 : 1  ω 5 c, C16 : 0 and iso-C15 : 0 . The new Spirosoma strains grew with 0–0.5 % (w/v) NaCl, at pH 6.5–8.0 and displayed optimum growth between 15 and 25 °C. Based on the results of phenotypic, genomic, phylogenetic and chemotaxonomic analyses, the new strains represent a novel species of the genus Spirosoma for which the name Spirosoma utsteinense sp. nov. is proposed. The type strain is R-68523 T (=LMG 31447 T =CECT 9925 T ).